Phytovaccines, a New Paradigm for Crop Protection: Towards a Sustainable Agriculture - Tomas Grau, Rodrigo Hernán (2022)
In this comment, we propose to incorporate the concepts “phytovaccines” to refer to bioproducts containing defense elicitors, and “phytovaccination” to the process of applying such phytovaccines to activate plants’ innate immune system. We bring support to these concepts based on the traditional process of human vaccination. We posit that plant defense elicitors are to plants what antigens are for humans, and that the elicitor-induced innate immune system in plants is to some extent similar to the immunization process triggered by an antigen in humans-saving the differences between both kinds of organisms. Both defense responses share many features, including an immunization agent (elicitor/antigen), the recognition of such agent by a receptor that initiates a cascade of reactions tending to activate a systemic response, that has a long-term effect and can passively be transmitted across the placenta to newborn infants in the case of humans, and to following generations of plants agamically propagated. We further compare phytovaccination to transgenic plants, as two valid biotechnological tools for crop protection, highlighting the benefits of the former. We encourage the academic and agricultural community in general and the plant-pathogen interaction community in particular, to incorporate the use of phytovaccines and phytovaccination into the biocontrol vocabulary.